Profile of Major Depressive Disorder Symptoms among Patients in Tehran - Rozita Davari; Elham Shirazi; Zahra Shahrivar; Amir Shabani; Vandad Sharifi; Javad Alagheband rad; Mitra Hakimshooshtary; Mehdi Tehranidoost; Homayoun Amini (Iranian Journal of Psychiatry, 2007)
Objectives: Culture may place a differential emphasis on particular emotions. The aim of this study is to find the most frequent symptoms in patients with major depressive disorder in Tehran. Method: 509 patients were recruited from 5 treatment settings. The sample was used from the project of assessing psychometric properties of CIDI in the Iranian population. The patients were evaluated by conducting clinical interviews and using DSM-IV criteria (American Psychiatric Association, 1994) for major depressive disorder. Results: Depressed mood (98.7%), sleep change (92.1%) and, fatigue / energy loss (89.4%) were the three highest-ranking symptoms. As cognitive factors, guiltiness and worthlessness were among the lowest ranking symptoms. There were no significant differences between men and women in frequency of symptoms with the exception of suicidal thoughts. Men had significantly higher suicidal thoughts than women. (P: 0. 01) Conclusion: Data were presented on the depressive symptomatology in population of Tehran. Key findings included a high rate of somatic symptoms in patients who suffered from MDD in this population.